Christian Tradition on Bitolszczyzna and in the Village Nowaci - Stojčevska-Antik’, Vera (Poznańskie Studia Slawistyczne, 2016)
The paper portrays the Macedonian folk Christianity, existing outside the official Church. Systematic scientific researches, also conducted nowadays, have shown that this phenomenon is not only still alive, but it is even growing – especially after 1989, when the Church in Macedonia started to recover. In the mainstream of popular Christianity, the Marian tradition is represented most strongly. Macedonians believe that the Mother of God since time immemorial until today has been personally involved in the construction of their church – as well in the spiritual as in the material meaning. An example could be the village Nowaci from Bitolszczyzna. Its population is convinced, that the church and monastery in the village were built on the order of Mary and according to her architectural project. The middleman between the Mother of God and the builders was supposed to be local clairvoyant Menka, called in a supernatural way to serve God.